Penerapan Solution-Focused Brief Counseling (SFBC) Untuk Mengurangi Tingkat Stress Akademik Siswa Kelas Xi Di Sman 18 Surabaya: Implementation of Solution-Focused Brief Counseling (SFBC) to Reduce Academic Stress Levels of Grade XI Students at Sman 18 Surabaya - Kartika Kusuma Dewi; Bakhrudin All Habsy; Nurudducha (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
Academic stress is the pressure or tension experienced by students as a result of the various demands and challenges related to their academic activities. Students often feel overwhelmed by the many assignments, projects, and exams that must be completed in a short time. Understanding academic stress and its impact is essential to developing effective interventions. Approaches such as Solution-Focused Brief Counseling (SFBC) can help students identify appropriate solutions and strategies to cope with their stress, improve mental health and academic performance. This study aims to evaluate the effectiveness of the implementation of SFBC. This study is a type of Guidance and Counseling Action Research with a qualitative method that was conducted in two cycles. The results showed that SFBC helped students identify goals, strengthen existing abilities, and find exceptions or moments when stress was not so pronounced. This intervention focuses on the future that students want and directs them to identify small steps that can bring positive changes in dealing with their academic stress. Through two cycles of intervention, students experienced significant improvements in time management and reduced duration of online gaming. The second cycle strengthened these findings with increased student readiness for exams and academic challenges. Keywords: Solution-Focused Brief Counseling, academic stress, academic performance, stress management